Job Satisfaction among School Health Nurses in Nepal - Ghimire, Madhavi Gautam; Devkota, Bhimsen (An ENDEAVOUR: Journal of Academia and Research, 2026)
“One School One Nurse Program” was introduced in Nepal as a pilot in 2018 by the Bagmati Provincial government. Gradually, the program has now expanded to all seven provinces. The core agenda of the program is to promote student’s health and learning while they are at school through the services provided by a school nurse. School nurses have been employed in many schools but their retention has emerged as big challenge. This study made an attempt to assess job satisfaction and the factors influencing job satisfaction status of school nurses through Herzberg’s (1959) motivation hygiene theory. This cross-sectional descriptive census survey was conducted among 519 school nurses of the community schools from August 2023 to February 2024. Data were collected through a structured questionnaire using the KoboToolbox platform. The study is based on Paula Stamp’s (1997) Index Work Satisfaction (IWS) questionnaire adapted and localized to match the context of Nepalese school nurses. The six-dimensions scale of school nurses job satisfaction, which demonstrated good internal reliability (α = 0.74) include three hygiene factors (pay, organizational policy and interaction) and three motivation factors (autonomy, task requirements and professional status). The measurement used a five-point Likert scale ranging from 1(strongly disagree) to 5 (strongly agree). The high mean score indicated stronger agreement and consequently, a higher level of satisfaction. Using SPSS v26 descriptive statistics, independent samples t-tests, one-way and ANOVA were carried out. Results revealed that, all the respondents were female with age range from 20 to 47 years (M = 27.43, SD = 4.24). The motivational factors composite mean (3.36) was found higher than hygiene factors mean (2.94). Among six factors, results demonstrated professional status (Mean = 3.62) as more satisfying factor and organizational policy as the dissatisfying factor. School nurses’, not having children, nurses with PCL degree, and nurses who felt training adequacy had statistically significantly linked to job satisfaction (p < 0.05). In conclusion, job satisfaction was found at moderate level. The study recommends the need to address organizational policy; contractual position, career ladder, work site support, a competitive incentive package, and in-service training in school settings to enhance retention.